2012
DOI: 10.1007/s11270-012-1322-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Grass Filters in Reducing Phosphorus and Sediment Runoff

Abstract: Surface water contamination can often be reduced by passing runoff water through perennial grass filters. Research was conducted in 2006 to 2008 to evaluate the size of cool season grass filters consisting primarily of tall fescue (Festuca arundinacea Schreb) with some orchard grass (Dactylis glomerata L.) relative to drainage area size in reducing runoff sediment and phosphorus (P). The soil was Pohocco silt loam Typic Eutrochrepts with a median slope of 5.5 %. The grass filters occupying 1.1 and 4.3 % of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…Seobi et al (2005) and Kumar et al (2012) determined that soil hydraulic conductivity values were four to 16 times higher in an agroforestry buffer than in the associated cropland or pasture. Reported trapping effectiveness values of upland and edge-of-field buffers vary widely among studies: from 41% to 100% for sediment and from 27% to 96% for total phosphorus (TP) (Dillaha et al, 1989;Daniels and Gilliam, 1996;Schmitt et al, 1999;Mayer et al, 1999;Lee et al, 2000;Blanco-Canqui et al, 2004;Vianello et al, 2005;Bhattarai et al, 2009;Caron et al, 2010;Al-wadaey et al, 2012).…”
mentioning
confidence: 99%
“…Seobi et al (2005) and Kumar et al (2012) determined that soil hydraulic conductivity values were four to 16 times higher in an agroforestry buffer than in the associated cropland or pasture. Reported trapping effectiveness values of upland and edge-of-field buffers vary widely among studies: from 41% to 100% for sediment and from 27% to 96% for total phosphorus (TP) (Dillaha et al, 1989;Daniels and Gilliam, 1996;Schmitt et al, 1999;Mayer et al, 1999;Lee et al, 2000;Blanco-Canqui et al, 2004;Vianello et al, 2005;Bhattarai et al, 2009;Caron et al, 2010;Al-wadaey et al, 2012).…”
mentioning
confidence: 99%
“…During the single snow event, concentrations of TP, DP, and PP were higher in both the 1.1% and 4.3% VBS plots than in the cultivated field containing 0% VBS. The 1.1% plot contained the highest concentrations of TP (4.8 mg•L −1 ) and DP (4.29 mg•L −1 ) of any sample during the study (Al-wadaey et al 2012).…”
Section: Snowmelt Runoff (%)mentioning
confidence: 96%
“…In a similar study in Nebraska, USA (Köppen-Geiger climate classification Dfa: humid continental climate with at least 1 month with temperatures <0°C), Al-wadaey et al 2012compared concentrations of TP, DP, and PP in surface runoff from cultivated fields that contained 0%, 1.1%, or 4.3% VBS area within the field. The authors point out that even in Nebraska, which does not experience the prolonged periods of snow cover and freezing temperatures that are typical of the northern USA or Canada, soils are frozen and vegetation is not actively taking up nutrients over winter (Al-wadaey et al 2012). Thus, runoff with limited infiltration is likely occurring, which has been shown to increase DP loads to surface waters.…”
Section: Snowmelt Runoff (%)mentioning
confidence: 99%
“…The P removal by vegetative buffers depends on buffer length, rate of inflow, type of vegetation, and density of vegetation coverage (Abu-Zreig et al, 2003). Al-wadaey et al (2012) found that vegetative filter of tall fescue (Festuca arundinacea Schreb) and orchardgrass did not affect P concentration but reduced DRP load by 66 to 73% and TP load by 68 to 76%. They concluded that a grass filter reduced sediment and P load through a reduction in runoff volume.…”
Section: Surface Water Qualitymentioning
confidence: 99%